The development and implementation of pathological parameters and molecular testing impact prognosis of colorectal adenocarcinoma - Midie Xu; Yaqi Li; Yingxue Liu; Jinjia Chang; Changming Zhou; Weiwei Weng; Hui Sun; Cong Tan; Xin Wang; Xu Wang; Meng Zhang; Shujuan Ni; et al. (Journal of the National Cancer Center, 2024)
Objective: This study aims to analyze how changes in pathological diagnosis practice and molecular detection technology have affected clinical outcomes for colorectal cancer (CRC) patients in Fudan University Shanghai Cancer Center (FUSCC). Methods: This retrospective cohort study analyzed 21,141 pathologically confirmed CRC cases diagnosed at FUSCC from 2008 to 2020. Patients were divided into five groups for different analytical purposes: (1) the before vs. since 2014 groups to analyze the influence of the changes in the classification criteria of pT3 and pT4 staging on the survival of patients; (2) the partial vs. total mesorectal excision (TME) groups to analyze whether evaluation of completeness of the mesorectum have impact on the survival of patients; (3) the tumor deposit (TD)(+)N0 vs. TD(+)N1c groups to analyze the influence of the changes in the pN staging on the survival of patients with positive TD and negative regional lymph node metastasis (LNM); (4) the before vs. since 2013 groups to analyze the influence of the changes in the testing process of deficient mismatch repair on the survival of patients; and (5) the groups with vs. without RAS/BRAF gene mutation testing to analyze the influence of these testing on the survival of patients. Patients’ clinicopathological parameters, including age at diagnosis, sex, tumor size, location, differentiation, mucinous subtype, TD, lymphovascular invasion, perineural invasion, tumor depth, LNM and distant metastasis, and tumor-node-metastasis (TNM) stage, were compared between groups. Kaplan-Meier analysis with log rank method was performed for patients’ overall survival (OS) and disease-free survival (DFS) analyses. Results: In pathological reports, there were three parameter changes that impacted patient outcomes. Firstly, changes in the pT staging criteria led to a shift of the ratio of patients with stage pT3 to stage pT4 from 1: 110.9 to 1: 0.26. In comparison to patients admitted before 2014 (n = 4,754), a significant difference in prognosis between pT3 and pT4 stages was observed since 2014 (n = 9,965). Secondly, we began to evaluate the completeness of the mesorectum since 2016. As a result, 91.0% of patients with low rectal cancer underwent TME (n = 4,111) surgery, and patients with TME had significantly better OS compared with partial mesorectal excision (PME, n = 409). Thirdly, we began to stage TD (+) LNM (-) as N1c since 2017. The results showed that N1c (n = 127) but not N0 (n = 39) can improve the prognosis of patients without LNM and distal metastasis. In molecular testing, there have been three and five iterations of updates regarding mismatch repair (MMR)/microsatellite instability (MSI) status and RAS/BRAF gene mutation detection, respectively. The standardization of MMR status testing has sharply decreased the proportion of deficient MMR (dMMR) patients (from 32.5% to 7.4%) since 2013. The prognosis of patients underwent MMR status testing since 2013 (n = 867) were significantly better than patients before 2013 (n = 1,313). In addition, detection of RAS/BRAF gene mutation status (n = 5,041) resulted in better DFS but not OS, for patients with stage I-III disease (n = 16,557). Conclusion: Over the past few decades, updates in elements in pathological reports, as well as the development of standardized tests for MMR/MSI status and RAS/BRAF gene mutations have significantly improved patient outcomes.